Never the wind - Dimitri, Francesco, 1981- (Titan Books, 2022)
1996 - Luca Saracino is thirteen and has been completely blind for eight months when his parents move to a Southern Italian farmhouse they dream of turning into a hotel. With his brother dropping out of university and the family reeling from Luca's diagnosis, they are chasing dreams of rebirth and reinvention. As Luca tells his story without sight - experiencing the world solely through hearing, smell, taste and touch - he meets the dauntless Ada Guadalupi, who takes him out to explore the rocky fields and empty beaches. But Luca and Ada find they can't escape the grudges that have lasted between their families for generations, or the gossiping of the town. And Luca is preyed upon by the feral Wanderer, who walks the vineyards of his home. As Luca's family starts to crack at the seams, Luca and Ada have to navigate new lands and old rivalries to uncover the truths spoken as whispers on the wind.